INVENTARISASI JENIS-JENIS TANAMAN PENGHASIL NEKTAR DAN POLEN SEBAGAI PAKAN LEBAH MADU Apis mellifera DI KECAMATAN KAIRATU KABUPATEN SERAM BAGIAN BARAT - Dominggus de Lima; J. S. A. Lamerkabel; Inggrid Welerubun (Agrinimal Jurnal Ilmu Ternak dan Tanaman, 2019)
The aim of this research was to determine the kinds of pollen producer plants, its population density and the number of cells contained bee bread (pollen) at bee nest. The observed variables were kinds of plants in general and its density, pollen producer plants, number of cells contained bee breed (pollen). Method used was survey techniques which conducted in four bee farms. The farms were naturally rich of some flowering plants such as Cambodia, asoka, bougainville; and some horticulture plants such as coconut Cocos mufifera), nutmeg (Myristisca frogranas houtt), palm (Arenga pinnata) ,cacao (Theobroma cacao), clove (Syzygiumaromatioum); some fruits plants such as guava(Psidium guajava), nut guava(Arnacidium occidentale), ambutan(Nephelium lappaceum), mango(mangifera indica), banana(Musa paradisiacal), langsat(Lansium domesticium). From the four bee farms chosen, there was revealed that Dusun Kawatu has the highest plant density, followed by respectively Negeri Hatusua, Negeri Waehatu and Negeri Kamarian. Also, Dusun Kawatu has more pollen producer plant varieties in comparison to the other three Negeri/ Dusun(s). However, bee farm in Negeri Kamarian has more number of cell contained pollen than other farms; followed respectively by bee farms in Negeri hatusua, Dusun Kawatu and Negeri Waehatu.